Pedestrian facilities for wheelchair users at UTC area Kuantan - Wan Nurul Nabilah, Wan Suhaimi (2017)
Wheelchair users have a lot of needs for them to live their daily life. They also faced with the difficulties to move around in the city area. Disregard the number of wheelchair users that use pedestrian facilities are small, they still have the rights to their needs. However, these facilities that are available for the wheelchair users are very limited and not according to standard specification.In order to encourage wheelchair users to be more independent, it is very important to make sure that access to public buildings, public parks and any area in the city area are suitable and comfortable for wheelchair users to move around. Hence, stakeholders such as architects, engineers, government and other parties are responsible to make sure all pedestrian facilities are provided for the wheelchair users. The effectiveness of the pedestrian facilities can be analysed by conducting the interview with a local authorities and audit at the Urban Transformation Centre (UTC) Kuantan area. The auditing was conducted by zoning to make sure the result was more detail and accurate. The identification of pedestrian facilities shows that there were most of the pedestrian facilities not follow the standard and specification and lack of pedestrian facilities for wheelchair users. This study also found, by proposing the new pedestrian facilities for wheelchair users will help to overcome the problem face by the wheelchair users.